Microbial Changes during Pregnancy, Birth, and Infancy - Nuriel-Ohayon, Meital; Neuman, Hadar; Koren, Omry (Frontiers in Microbiology, 2016)
Several healthy developmental processes such as pregnancy, fetal development and infant development include a multitude of physiological changes: weight gain, hormonal and metabolic changes, as well as immune changes. In this review we present an additional important factor which both influences and is affected by these physiological processes- the microbiome. We summarize the known changes in microbiota composition at a variety of body sites including gut, vagina, oral cavity and placenta, throughout pregnancy, fetal development and early childhood. There is still a lot to be discovered; yet several pieces of research point to the healthy desired microbial changes. Future research is likely to unravel precise roles and mechanisms of the microbiota in gestation; perhaps linking the metabolic, hormonal and immune changes together. Although some research has started to link microbial dysbiosis and specific microbial populations with unhealthy pregnancy complications, it is important to first understand the context of the natural healthy microbial changes occurring. Until recently the placenta and developing fetus were considered to be germ free, containing no apparent microbiome. We present multiple study results showing distinct microbiota compositions in the placenta and meconium, alluding to early microbial colonization. These results may change dogmas and our overall understanding of the importance and roles of microbiota from the beginning of life. We further review the main factors shaping the infant microbiome- modes of delivery, feeding, weaning, and exposure to antibiotics. Taken together, we are starting to build a broader understanding of healthy vs. abnormal microbial alterations throughout major developmental time-points.